Analysis of Cerebrovascular Autoregulation Reactivity Index Electronic Monitoring Methods - Ragauskas, A.; Kalvaitis, E.; Petkus, V.; Daubaris, G.; Depreitere, B. (Elektronika ir Elektrotechnika, 2011)
Pressure reactivity index (PRx), which is a moving linear correlation (or Pearson's correlation) between slow waves of ABP and ICP is used as an estimator of the human brain cerebrovascular autoregulation state. Slow ICP and IBP waves were modeled and PRx was calculated by widely used calculation method. It was shown, that existing PRx calculation method gives non- linear PRx distortions comparing with phase shift of ABP and ICP slow waves. It was proposed PRx calculation method, which eliminates non-linear phase demodulator (Pearson's correlation coefficient calculator), brought in monitoring of human brain cerebrovascular autoregulation. Ill. 7, bibl. 18 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.687